Dental splint treatment in bruxism induced by anti-seizure drug: case report - Chuquimez Ventura, Casimira Valeria (2020)
Signs of tooth wear and grinding are associated with bruxism, which is commonly observed in dental offices. Here, the authors describe a case of bruxism probably induced by the anti-seizure drug Valpromed®, that was successfully treated with a dental splint. A man was attended in the dental clinic for improvement of dental aesthetics. On clinical examination moderate overwear of the occlusal surfaces of molars was observed associated with a history of nightly grinding, characteristic of sleep bruxism. Approximately 5 months previously, the patient had started therapy with Valpromed® due to episodes of migraine. The drug had been prescribed by a neurologist to prevent convulsions since the patient had had neurocysticercosis during childhood. Based on the advice of an oral rehabilitation specialist and the literature reviewed, it was concluded that the presence of bruxism in this patient may be attributed to the therapy with the anti-seizure medication. Although the patient is still under controls, the dental splint seems to be a promising approach for the treatment of this condition. The patient was treated with a minimally invasive dental splint and is monitored periodically, showing good results.